Health Workers' Job Satisfaction in the Era of National Health Insurance: Services and Working Conditions - Dwi Noerjoedianto; Dian Meisafitri; Hubaybah (Chakra Brahmanda Lentera Institute, 2022)
Background: A person's perception of their level of justice (equity) at work is reflected in their level of job satisfaction. The nature of the work, salary, supervision, and relationships among coworkers are all factors that affect how satisfied one is with one's job. The number of patients treated by the Puskesmas in the National Health Insurance (JKN) is rising, with 586,893 persons (94.55%) in Jambi City enrolled as JKN participants at the Puskesmas. This study aimed to ascertain the relationship between services and working circumstances and the job satisfaction of healthcare professionals at the Jambi City Health Center in 2021 during the National Health Insurance (JKN) era. Methods: A cross-sectional design method was used in this investigation. The study's population comprised six hundred fifty-three healthcare professionals, and 92 respondents were nurses. Services and working circumstances are the study's independent variables, while job conditions are its dependent variable. Questionnaires are measurement devices. Univariate and bivariate data analyses were performed (using the chi-square test = 0.05). Results: Determine the association between the independent and dependent variables using bivariate Chi-Square analysis. The findings indicated that the relationship between job satisfaction and services had a p-value of 0.037, where 0.05. The correlation between favourable working conditions and job satisfaction is 0.023, with 0.05 as the reference value. Conclusion: In conclusion, there is a correlation between the services provided and the job happiness of healthcare professionals at the Jambi City Health Center and between working circumstances and job satisfaction.